Codificación de mortalidad con CIE-11 en Chile: principales resultados y perspectivas para su implementación. - Montecinos, Paulina Vera; Pacheco, Jorge; Guinez-Molinos, Sergio; Piedra, Daily; Velozo, Lorena; Fuentes, Andrés; Carmona, Marcela; Landabur, Alejandra; Suárez, Pamela; Leighton, Paulina (Pan American Journal of Public Health, 2025)
Objective. To evaluate the usability of the International Classification of Diseases, 11th Revision (ICD-11) and its concordance and comparability with ICD-10, the version in use. ICD-11 introduces greater granularity than ICD-10, is designed for digital environments, and offers improvements over the previous version. Methods. Two thousand medical death certificates for year 2020 were selected by proportional stratified sampling. Two expert coders and a gold standard team coded the records using the official ICD-11 tool. Concordance between gold standard and expert coders was assessed for immediate, underlying, and principal cause of death. Distribution by chapter was compared for ICD-11, ICD-10 in the original database, and ICD-10 mapped from ICD-11. Results. Concordance with clinical accuracy ranged from 37% for principal cause of death to 76% for immediate cause. Agreement on base codes ranged from 73% for principal cause to 86% for immediate and underlying causes. Cohen's kappa for principal cause was 0.68 (95% CI: 0.64 - 0.72) for coder 1 and 0.76 (95%CI: 0.73 - 0.80) for coder 2, which is considered significant concordance. The distribution of principal cause for ICD-10 and for ICD-10 mapped from ICD-11 was similar. Conclusions. There is adequate concordance and comparability between ICD-11 and ICD-10. The tool has high usability, which confirms the feasibility of ICD-11 implementation in Chile, and underlines the need for continuous training and technological improvement.